5 scientific problems for immersive interactions design within virtual reality applications development pipeline - Maksom, Zulisman; Norasikin, Mohd Adili; Abdul Rahim, Nurul Aiman (Little Lion Scientific Islamabad Pakistan, 2024)
Virtual reality (VR) has emerged as a transformative technology with multifaceted applications across gaming, education, and industry. It is also align with Sustainable Development Goal (SDG) in Industry, Innovation, and Infrastructure, by fostering innovation and technological advancement. However, the inherent complexity of VR application development presents challenges, particularly in immersive interaction design within the development pipeline. In this review, we emphasize the importance of addressing five scientific problems pertaining to interaction design within the VR application development pipeline. By shedding light on these challenges, we aim to stimulate discussion, propose solutions, and ultimately contribute to the advancement of VR techniques and applications, with a particular focus on immersive interaction design. We endeavor to support the realization of SDGs by harnessing VR technology to drive innovation, enhance accessibility, and promote sustainable development across various sectors.